Penerapan Model Pembelajaran Berbasis Proyek Dengan Pendekatan Sains Teknologi Masyarakat Untuk Meningkatkan Penguasaan Konsep Dan Sikap Peduli Siswa Terhadap Lingkungan - Ani Hanifah; Usep Soetisna; Anna Fitri Hindriana (Program Studi Pendidikan Biologi, Sekolah Pascasarjana Universitas Kuningan, 2018)
Background of this research was lowmastery of concept to Sciencesubject in SMP Negeri 3 Sindang Indramayu that was caused of the learning method that were not the student centered and low student attention toward the environment conservation and clean. The purpose of the research was to know the application Project Based Learning Model with the Science of Society Technology Approach to increase the mastery of concept and the student attention attitude toward the environment. The method of the research is Quasi Experimentwith Pretest-Posttest Control Group Design. The population of this research wereall the students in grade VII of SMP Negeri 3 Sindang in the academic year 2017/2018 that was consist of 8 classrooms in the total of 256 students. The sampling technique of the research was Purposive Random Sampling. The class that was become a sample was grade VIIC (the control class PJBL without The Science of Society Technology Approach) that was consist of 32 students. And grade VIIB (the experiment class PJBL withThe Science of Society Technology Approach) that was consist of 32 students. The instrument that was used in this research was multiple choice test, question naire and journal observation. The result of this research showed that there werethe raising mastery of concept and the student attention attitude toward the environment after applied the project based learning model withThe Scienceof Society TechnologyApproachKeywords: Project Based Learning Model; The Scienceof Society Technology; The Mastery of Concept